Lewis and Clark in Missouri - Rogers, Ann (University of Missouri Press, 2002)
"In May 1804 Meriwether Lewis, William Clark, and the Corps of Discovery embarked on a seven-thousand-mile journey with instructions from President Thomas Jefferson to ascend the Missouri River to its source and continue on to the Pacific. They had spent five months in the St. Louis area preparing for the expedition that began with a six-hundred-mile, ten-week crossing of the future state of Missouri. Prior to this, the explorers had already seen about two hundred miles of Missouri landscape as they traveled up the Mississippi River to St. Louis in the autumn of 1803." "Lewis and Clark in Missouri focuses on the Missouri chapter of their epic journey, a portion of the story that has been slighted in other accounts. Ann Rogers uses the journals kept by members of the Corps along with many other primary source materials, providing a firsthand perspective on the people, plants, wildlife, rivers, and landscapes."--Jacket.